Regime of Contraventions and Sanctions Related to VAT Tax Declarations - Boiţă, Marius; Dumiter, Florin Cornel; Ajtay, Eduard (Journal of Legal Studies, 2022)
In order to better collect taxes and combat fraud and tax evasion by strengthening the national legislative framework, a number of regulations and reports have been put in place for monitoring the declaration of all economic operations between partners in a regulated free market. The provisions adopted in the field of taxation in conjunction with the accounting report provided, respectively reported by the entities to the tax authorities, are applied for the correct assessment of their activity in order to combat the practices of tax avoidance, tax fraud, and tax evasion. This study does not analyze the fiscal policy as a whole, this paper addresses the regime of contraventions and sanctions, as well as the repercussions of non-declaration or incomplete or erroneous declaration of the Recapitulative Statements on intra-Community supplies/acquisitions/services (code D390) and Informative declarations on deliveries/services and purchases made in the national territory (code 394), related to value-added tax.